Benzoylcyclopropane Derivatives from Hypoxis hemerocallidea Corms - Zulfiqar, Fazila; Pandey, Pankaj; Tripathi, Siddharth K.; Ali, Zulfiqar; Chittiboyina, Amar G.; Khan, Ikhlas A. (Planta Medica, 2021)
Two monobenzoylcyclopropane (hypoxhemerol A (1) and hypoxhemeroloside G (2)) and three dibenzoylcyclopropane (hypoxhemerol B (3), hypoxhemeroloside H (4), and hypoxhemeroloside I (5)) derivatives were isolated from the hydro-alcoholic extract of Hypoxis hemerocallidea corms. This is the first instance where benzoylcyclopropane analogs were isolated from any natural source. Structure elucidation was mainly based on 1D- and 2D-NMR and HRESIMS data. The absolute configuration (2R, 4R) of 1 was determined via NOESY NMR and experimental and calculated ECD data analyses. Compounds 1–5 and 11 recently reported metabolites (hypoxoside, obtuside A, interjectin, acuminoside, curcapicycloside, and hypoxhemerolosides A – F) were screened for in vitro antimicrobial activity against various bacterial and fungal strains. Curcapicycloside and acuminoside exhibited antibacterial activity against Escherichia coli with 78 and 79% inhibition at 20 µg/mL, respectively. Hypoxhemeroloside A showed mild antifungal activity against Cryptococcus neoformans with 63% inhibition at 20 µg/mL.
Keywords: Hypoxis hemerocallidea; hypoxidaceae; benzoylcyclopropane; hypoxhemerol; hypoxhemeroloside; antimicrobial